2013
DOI: 10.1159/000355079
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Institutionalization of Dementia Patients in Mild and Moderate Stages: A 4-Year Prospective Analysis

Abstract: Background: Institutionalization is the most important milestone in the care of dementia patients. This study was aimed at identifying relevant predictors of institutionalization in a broad empirical context and interpreting them on the basis of the predictor model proposed by Luppa et al. [Dement Geriatr Cogn Disord 2008;26:65-78]. Methods: At the start of this study, 357 patients with mild to moderate dementia were examined by their general practitioners, and a telephone interview was conducted with their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 95 publications
4
108
1
2
Order By: Relevance
“…On the contrary, cohabitation protects against DTI. This finding is in accordance with other studies [8, 12] and suggests that living together has a more important influence on DTI than the type of relationship within the dyads, which was not independently associated. Indeed, it is to be expected that more time, organization, and effort is needed to provide informal care when not sharing the same household.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the contrary, cohabitation protects against DTI. This finding is in accordance with other studies [8, 12] and suggests that living together has a more important influence on DTI than the type of relationship within the dyads, which was not independently associated. Indeed, it is to be expected that more time, organization, and effort is needed to provide informal care when not sharing the same household.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning non-modifiable factors, corresponding to previous work, it was concluded that caregiver age [11, 12, 35], professional situation [40], and educational level [12] were positively associated with DTI. The latter can be explained by the fact that highly educated CG may be better informed about the possibilities, may have less problems to pay for institutional care, and may be less prepared to adapt or give up their professional career for caregiving.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research also indicates that persons with dementia experience more care transitions than others (Coleman & Boult, 2003) and have a higher risk of adverse events such as medication errors, hospitalizations, stress and anxiety, and other problems than those without the disease (Manderson et al, 2012). Although most individuals with dementia are cared for at home, the progression of the disease often leads to higher levels of care (McCabe, You, & Tatangelo, 2016), with increased likelihood of institutionalization over time (Eska et al, 2013).…”
Section: Introductionmentioning
confidence: 99%